Analisis Dampak Kebingaran Mesin Pesawat Bagi Petugas Marshaller di Bandar Udara Internasional Blimbingsari Banyuwangi - Brendy Setya Saputra; Gallis Nawang Ginusti (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The number of aircraft in Indonesia drives both the national and global aviation industries. The government and airport management must enhance the quality, performance, safety, security, and economic development of airports. Blimbingsari International Airport in Banyuwangi supports air transportation in Rogojampi, Banyuwangi; however, advancements in aviation facilities can increase air pollution and noise, disrupting community activities and degrading environmental quality. Aircraft movements require coordination, including the role of marshallers who must use Personal Protective Equipment (PPE) and adhere to Occupational Health and Safety (OHS) protocols for safety. Noise reduction efforts at the airport must comply with the maximum limit of 55 dBA in residential areas. This qualitative case study investigates the impact of aircraft engine noise on the hearing of marshallers at Blimbingsari International Airport in Banyuwangi. Primary data were obtained from direct observation and interviews, while secondary data were sourced from regulations and relevant documents. The findings indicate that noise levels at the airport range from 34-66 dB(A) and do not significantly impact the health of nearby residents or operational staff. The authors recommend that the airport management regularly check the readiness of field staff, enhance equipment and the availability of first aid kits (P3K) in the AMC Unit, and ensure the quality of PPE and health guarantees for operational staff, particularly in the AMC division (Marshallers, Ramp Handling).